The effect of teacher leadership and school climate on students’ learning outcomes - Carolus Patampang; Patrio Tandiangga; Frans Fandy Palinoan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Student learning outcomes can be influenced by several factors. Some of them are teacher leadership and school climate factors. This study aims to determine the significance of teacher leadership and school climate on student learning outcomes. The method used in this research is a survey research method. The population from this research includes all class X students at Cendrawasih Catholic High School.There are 106 students in class X and consisting of 46 female students and 60 male students. Sampling in this study was carried out by means of simple random sampling. The sample size was determined using Issac & Michael’s table. Sampling of this study were 84 and consisting of 38 female students and 46 male students. Data collection techniques in this study were questionnaires and documentation. The data obtained were then analyzed using the Multiple Linear Regression analysis technique. The results of this study indicate that teacher leadership and school climate simultaneously have a positive and significant influence on the learning achievement of Class X Cenderawasih Catholic High School students in the subject of Catholic Religious Education as indicated by the values of the regression coefficients and correlation coefficients which are positive. The implication of this research is to provide enlightenment to all teachers and everyone involved in the world of education that creating a positive school climate and good teacher leadership will have a very good impact on student learning outcomes.